Attitude dan Financial Knowledge Menjadi Salah Satu Faktor Dalam Pengambilan Keputusan pada UMKM - Rusdi Hidayat; Acep Samsudin; Minanti Dwi Setianingrum; Badi Atus Sa’adah; Dini Annisa Pelupessy; Wirda Fitria Sahila (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
This study aims to determine the effect of Financial Attitude and Financial Knowledge on decision making in Micro, Small and Medium Enterprises (MSMEs). The research method used is the study of literature and literature. Where the author uses various journals whose discussion is still relevant to be used as reference material for making this journal. The results of the study show that investment decisions for MSMEs are not affected by financial feasibility and decision-making when returning has a positive and significant effect on financial attitudes and Financial Knowledge. This means that the better the Financial Knowledge and Financial Attitudespossessed by SME owners, the more confident they will be in making financial decisions. This research is expected to be a reference for other researchers. Keyword: attitude, financial, decision making, SMEs